Pengaruh Penggunaan Padu Terhadap Sifat Fisik, Kimia dan Organoleptik Jelly Drink Nanas (Ananas comosus L. Merr) - Chi Chi Nur Anisa Basiru; Jenny E A Kandou; Lucia Cecilia Mandey; Yoakhim Oessoe (JURNAL BIOS LOGOS, 2023)
This study aims to analyze the physical, chemical characteristics and test the organoleptic acceptance of pineapple jelly drink with different concentrations of honey. This study used a completely randomized design (CRD) method which consisted of one factor, namely variations in the honey formula (11%, 13%, 15%, 17%). The results showed the physical and chemical characteristics of pineapple jelly drink as follows: suction power 3.95-4.97, syneresis 0.35-2.65%, pH 3.00-5.00, vitamin C 2.35-4, 13mg/g, reducing sugar 6.41-9.86%. Organoleptic test results Pineapple jelly drink with the concentration of adding honey that is most preferred by panelists with criteria for color, taste, aroma, texture is the F2 treatment, namely 13% honey concentration with an average color value of 5.06% (rather like), taste 5.06 % (rather liked), aroma 4.58% (rather liked), texture 4.92% (rather liked). Keywords: Jelly Drink, Pineaapple, Honey.